Multi-objective optimization of the matching beamline for external injection into a laser-driven plasma accelerator. (July 2020) - Panofski, E; Assmann, R W; Svystun, E N
Abstract: Accelerators based on laser plasma wakefield acceleration are of great interest for a new generation of compact machines. External injection of an electron beam from an RF injector into a plasma accelerating stage has the advantage that a well-controlled and fully characterized beam can be used. The matching of the electron bunches into an accelerating plasma wakefield places high demands on the electron beam quality. The electron beam size must be extremely small to match the field structure inside the plasma wake. The short period of the accelerating field in the plasma requires a bunch length in the (sub-)fs range. These electron beam properties result in a high electron density and strongly space charge dominated bunches. The beamline upstream of the plasma must be able to control the significant effect of space charge on the bunch and to transversely match the beam to the focusing fields of the plasma. Further constraints to the beamline design are given by the in-coupling of the high-power drive laser and the implementation of diagnostic tools. Choosing suitable settings for the beamline elements in order to match the beam thus poses a great challenge. Using multi-objective optimization, suitable settings for the beamline elements can be extracted from Pareto optimum solutions. The development of a universal multi-objective optimization algorithm for beamline matching as well as first optimization results are presented.